Gender, Politics, and the State, and the Māori - Houkamau, Carla (The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
A diversity of perspectives and wide variety of cultural and social features characterize Māori society and there is no one consensus view held by Māori in relation to gender roles, political orientations, or Māori/government (or state) relations. Both Māori women and men have shared in the struggle to assert Māori resistance to colonial encroachment and one gender cannot be elevated over the other. Moreover, Māori views and perspectives on the different roles of Māori men and women are contested and differ tribally and between individuals. This entry describes aspects of precolonial Māori society that shaped traditional values and discusses key sociohistorical factors shaping gender roles among Māori. A focus on the contribution of Māori women to Māori development and advancement is offered. The relationship between Māori identity, culture, and the New Zealand government (or state) is highlighted throughout.
Keywords: crown policy; cultural practices; gender; identity; mana wāhine

Identity and socio-historical context : transformations and change among Māori women [Doctoral dissertation, University of Auckland] - Houkamau, Carla (2023)
ABSTRACT Several writers have argued that New Zealand’s colonial history has thwarted optimal identity development among Māori (Awatere, 1984; Lawson Te-Aho, 1998a; 1998b). In recent decades the view that Māori identity may be restored via enculturation has gained widespread acceptance (Broughton, 1993; Edwards, 1999). Recent research indicates, however, that many Māori perceive their identities in ways that differ from the enculturated ideal (Borrell, 2005; Te Hoe Nuku Roa, 1996; 1999). Relatively little is known of the diverse interpretations that comprise ‘alternative’ Māori identity forms. This thesis aims to contribute to current understandings of Māori identity by exploring identity change across three generations of Māori women. For the purposes of the research, identity was treated as ‘held’ within personal life-stories and transformations were investigated by comparing the life-stories of 35 Māori women from different age groups. Attention was given to the impact of three socio-historical processes on identity: the mass migration of Māori from rural to urban locations after the 1950s, the drive towards Māori assimilation which underpinned Government policy towards Māori until the late 1960s, and the Māori political and cultural renaissance which gathered momentum in New Zealand from the 1970s. Data analyses found participants born prior to urbanisation evaluated their Māori identities positively and this seemed to reflect their isolation from Pākehā and exposure to competent Māori role models during their formative years. Participants aged between 35 and 49 expressed disharmony and tension around their Māori identities which many attributed to their early exposure to negative evaluations of Māori people. ‘Post-renaissance’ Māori, aged between 18 and 35, reported prizing their cultural distinctiveness from a young age and affirmed Māori political, cultural and social equality despite what they perceived as enduring Pākehā prejudice. This interpretation appeared to reflect their early exposure to educational experiences which imparted a sense of cultural pride and a national news media which publicised Māori political activism. Women’s life-stories reveal distinct intergenerational differences, a multiplicity of interpretations of Māori identity not widely articulated in literature, and the need to expand current paradigms of Māori identity to incorporate the individuality of group members.
Keywords: crown policy; identity; urbanisation; wāhine māori